LIQUID SMOKE PRODUCTION FROM PALM KERNEL SHELL PYROLYSIS: COMPARING COLD AIR AND CONVENTIONAL CONDENSATION METHODS - Sipahutar, Riman; Bizzy, Irwin; Hidayati, Baiti (Asosiasi Peneliti Sriwijaya, 2025)
Gas condensation is one of the problems in the liquid smoke production process. Uncondensed gas will have an impact on the liquid smoke produced and air pollution. Here, several methods are applied to determine the percentage level of liquid smoke produced by the gas condensation process. The condensation method uses conventional normal water, gas condensation using cold water, and gas condensation using cold air. The raw materials used are oil palm shells with a size of -4+5 mesh, a pyrolysis temperature of 300-4000C, and a liquid smoke production process for 300 minutes. Based on the test results, gas condensation occurs optimally in the cold air method, with the results of 22% liquid smoke, 64% charcoal, and 14% non-condensed gas. Compared with the condensation of the standard water method, the condensation method of cold air is superior to 36.36% for liquid smoke to minimize air pollution by up to 48%. The results of this study indicate that temperature and fluid effect the effectiveness of the gas condensation process, thereby increasing the yield of liquid smoke and reducing air pollution during the liquid smoke production process.